Parenting during the COVID-19 Lockdown in Portugal: Changes in Daily Routines, Co-Parenting Relationships, Emotional Experiences, and Support Networks - Ana P. Antunes; Silvana Martins; Laura Magalhães; Ana T. Almeida (Children, 2021)
The COVID-19 pandemic challenged parental resources pertinent to coping with lockdowns. The main objective of this work was to study parenting during the COVID-19 lockdown. Specifically at focus were parental behaviors concerning key domains for the family (daily routine, co-parenting, emotional experience, and support network) and changes related to the pandemic and associated with the parents’ employment statuses. An online survey was carried out through an ad hoc questionnaire where participants completed questions about their sociodemographic data and rated how much their family routines, their co-parenting relationship, their emotional experiences, and the support available in the family network varied on a 5-point scale. The participants included 1384 parents, of which 286 responded to open questions regarding impactful experiences during the lockdown. The results showed differences in daily routine, co-parenting, emotional experience, and support network according to the parents’ employment statuses. Between-group comparisons showed that at-home parents caring for children with governmental aids generally revealed more positive parenting behavior changes, while at-home parents who were teleworking reported more difficulties in parent-child activities and co-parenting. Furthermore, the content analysis of the data confirmed how important themes such as family dynamics, professional activities, and the relationship with the school community were throughout the participants’ accounts of gains and losses. Overall, parents’ employment statuses are associated with diverse experiences during lockdown. The COVID-19 pandemic highlighted the importance of family resources and parental resilience, particularly during circumstances jeopardizing the ever-sensitive work-family balance.